Strategi Pemasaran Digital Berbasis Media Sosial Untuk Penguatan Kapasitas SDM Usaha Mikro di Kampung Bukit Makmur, Kalimantan Timur - Muh Irshan Sachrir; Ulul Azmi Mustari (Nusantara Innovation Journal, 2025)
The advancement of digital technology has changed various sectors of life, including how micro-entrepreneurs market their products and services. This study explores how micro-entrepreneurs in Kampung Bukit Makmur, East Kalimantan, utilize social media as a promotional tool in the digital era. This study uses a qualitative approach with a descriptive analysis method. Data were collected through interviews with micro-entrepreneurs and reinforced with references to related literature. The study results show that social media, especially WhatsApp, is the primary medium for promotion through the Status feature and community groups. Social media effectively expands market reach, reduces promotion costs, and facilitates direct interaction with consumers. However, micro-entrepreneurs still face challenges in the form of limited digital literacy, unequal internet access, and minimal skills in creating creative content. These findings provide important insights into the opportunities and obstacles micro-entrepreneurs face when using social media in rural areas. The implication is that a more targeted and contextual digital literacy mentoring and training program is needed to help them optimally adapt to the dynamics of the digital market.